Protection, health seeking, or a laissez-passer: Participants' decision-making in an EVD vaccine trial in the eastern Democratic Republic of the Congo. (April 2023) - James, Myfanwy; Kasereka, Joseph Grace; Kasiwa, Benjamin; Kavunga-Membo, Hugo; Kambale, Kasonia; Grais, Rebecca; Muyembe-Tamfum, Jean-Jacques; Bausch, Daniel G.; Watson-Jones, Deborah; Lees, Shelley
Abstract: During the 10th Ebola virus disease (EVD) epidemic in the eastern Democratic Republic of the Congo (DRC) (2018–2020), two experimental EVD vaccines were deployed in North Kivu. This province has been at the centre of conflict in the region for the last 25 years. Amidst ambivalence towards protracted foreign intervention and controversy about introducing two experimental vaccines, the existing literature has focused on mistrust and 'resistance' towards the Ebola response and vaccines. In this article, we examine why people in the eastern DRC did decide to volunteer for a trial of a second EVD vaccine in North Kivu, despite the controversy. Drawing on ethnographic observation, interviews, and focus groups with trial participants conducted between September 2020 and April 2021, we analyse three motivations for participating: protection, health seeking, and expectations surrounding travel requirements. We make three points. First, participation in vaccine trials may be understood locally to have advantages which have not been considered by the trial, because they go beyond medical considerations and are specific to a particular social setting. Second, despite much of the literature focusing on a causal relationship between rumours and 'vaccine hesitancy', some rumours may in fact encourage participation. Third, material objects associated with trial participation - such as participant vaccine cards - can hold social and political meaning beyond the confines of the vaccine clinic, and influence decisions surrounding participation. Empirical investigation of how medical interventions become entangled in political economies is essential to understanding the perceived functions of participation, and thus the reasons why people volunteer in clinical trials. Participants' narratives about their decision-making provide an insight into how international bioethical debates interact with, but may also stand apart from, the situated social and economic realities driving decision-making around clinical trials on the ground. This highlights the need for ethical approaches that foreground the political, social, and economic context. Highlights: Study of participant decision making in a second Ebola vaccine trial. Situated social and economic realities shape participant decision making. Rumours can in fact encourage participation in clinical trials. Gap exists between international bioethical debates and participant motivations. Need for ethical approaches that consider political, social, and economic contexts.